Stochastic strategic planning of open-pit mines with ore selectivity recourse. Issue 1 (2nd January 2018) - Navarra, A.; Montiel, L.; Dimitrakopoulos, R.
Abstract: Stochastic mine planning algorithms have been extended to better represent ore selection decisions. Under geological uncertainty, existing algorithms generate plans that may violate the mineral processing capacity; under such geological scenarios, the excess ore undergoes a recourse action which is not as profitable as regular processing, hence decreasing the net present value. This decrease has previously been represented as a penalty on excess ore, which may not accurately represent actual operations. The new framework considers the most typical recourse: increasing the cut-off grade into the mineral process. This approach is demonstrated by adapting the VND algorithm of Lamghari et al.